2016
DOI: 10.1177/0193945916665814
|View full text |Cite
|
Sign up to set email alerts
|

Abstracting ICU Nursing Care Quality Data From the Electronic Health Record

Abstract: The electronic health record is a potentially rich source of data for clinical research in the intensive care unit setting. We describe the iterative, multi-step process used to develop and test a data abstraction tool, used for collection of nursing care quality indicators from the electronic health record, for a pragmatic trial. We computed Cohen’s kappa coefficient (κ) to assess inter-rater agreement or reliability of data abstracted using preliminary and finalized tools. In assessing the reliability of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…is usually requires a requirement analysis to determine the entity type, the relationship between the entities, and their attribute set codes and finally build the E-R model. Because each entity has many attributes, only the main related attributes are listed in each entity [19]. e E-R model of the data mining model constructed in this research is shown in Figure 2.…”
Section: Optimal Design Of Data Mining Modelmentioning
confidence: 99%
“…is usually requires a requirement analysis to determine the entity type, the relationship between the entities, and their attribute set codes and finally build the E-R model. Because each entity has many attributes, only the main related attributes are listed in each entity [19]. e E-R model of the data mining model constructed in this research is shown in Figure 2.…”
Section: Optimal Design Of Data Mining Modelmentioning
confidence: 99%
“…Consensus exits among authors on the use of standardized and electronic documentation to support the nursing process and to improve the quality of nursing documentation (Hillestad et al., ; Mahler et al., ; Müller‐Staub, Needham, Odenbreit, Ann Lavin, & Van Achterberg, ; O'Brien et al., ; Seaman et al., ; Yu, Qiu, & Crookes, ). Nurses globally are embracing the advancement in Information and Communication Technology (ICT) to meet the changing needs of the society across culture through effective documentation which promotes accuracy of information and continuity of care (Habibi‐Koolaee, Safdari, & Bouraghi ; Kahouei, Mohammadi, Majdabadi, Solhi, Parsania, Oghani & Firozeh, ; Sockolow, Liao, Chittams, & Bowles, ; Yu, Hailey, & Li, ).…”
mentioning
confidence: 99%
“…The first standpoint indicates the degree of readiness of nursingsensitive indicators to be used in care quality assessment. Previous research presents ample evidence of the use of nursing-sensitive indicators corresponding to the established expressions found in our study, such as experiences of pain or prevalence of pressure injuries (Seaman et al, 2017). These examples also include research focusing on extracting information related to pain management, ranging from risk identification to the evaluation of analgesic effect or pain prevalence (Nomura et al, 2021).…”
Section: F I G E 2 Unestablished Expressions Related To Nursing Care ...mentioning
confidence: 65%
“…This indicates that increasing nurse competence and resources may improve the benefits of both primary and secondary use of EHR data. (Seaman et al, 2017). Automated data extraction methods would therefore highly benefit from the introduction of NLP to support the secondary use of EHR data.…”
Section: F I G E 2 Unestablished Expressions Related To Nursing Care ...mentioning
confidence: 99%
See 1 more Smart Citation